PENERAPAN METODE FUZZY TIME SERIES-MARKOV CHAIN DALAM PERAMALAN CURAH HUJAN SEBAGAI JADWAL TANAMAN PADI - Yusra Habibah Laily; Fibri Rakhmawati; Ismail Husein (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Rice plants are plants that depend on rainfall because it affects the productivity and quality of rice plants. The purpose of this study is to forecast rainfall in order to determine the right time to plant rice. This study uses the Fuzzy Time Series-Markov Chain method which is a hybrid Fuzzy Time Series method with a markov chain stochastic process. This study uses monthly rainfall data in Kab. Mandailing Christmas from January 2017- December 2022 in mm (millimeter). The data was taken online from the official BPS-North Sumatra website. The results showed that the Fuzzy Time Series-Markov Chain method has a MAPE value of 4.30% which means it has a very good forecasting accuracy value because it is less than 10%. So it can be concluded that forecasting with FTS-MC is a fairly good method in predicting rainfall so that it can forecast for the following month.